2016
DOI: 10.1038/srep28870
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-based side view flow chamber reveals tether-to-sling transition in rolling neutrophils

Abstract: Neutrophils rolling at high shear stress (above 6 dyn/cm2) form tethers in the rear and slings in the front. Here, we developed a novel photo-lithographically fabricated, silicone(PDMS)-based side-view flow chamber to dynamically visualize tether and sling formation. Fluorescently membrane-labeled mouse neutrophils rolled on P-selectin substrate at 10 dyn/cm2. Most rolling cells formed 5 tethers that were 2–30 μm long. Breaking of a single tether caused a reproducible forward microjump of the cell, showing tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…2). Tethers are long submicrometer-diameter membrane tubes that are generated upon pulling the microvilli from the cell body if the PSGL-1/P-selectin bond experiences a force exceeding ;30 pN [39,72,73]. Tethers form behind the rolling neutrophil and lead to slower and more uniform rolling of neutrophils in response to changes in wall shear stress.…”
Section: Subcellular Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Tethers are long submicrometer-diameter membrane tubes that are generated upon pulling the microvilli from the cell body if the PSGL-1/P-selectin bond experiences a force exceeding ;30 pN [39,72,73]. Tethers form behind the rolling neutrophil and lead to slower and more uniform rolling of neutrophils in response to changes in wall shear stress.…”
Section: Subcellular Structuresmentioning
confidence: 99%
“…2A). Tethers do not retract, but detach from the selectin substrate, swing around the cell, and appear as slings in front of the cell [39,73]. Thereby, 15% of all breaking tethers form slings with an average length of 22 mm.…”
Section: Subcellular Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there are only a handful of direct experimental observations of membrane heterogeneities along nanotubes in cells [44]. While it is easy to imagine the beaded morphologies in in vitro studies [20,45], it remains to be seen if such morphologies will be observed in cells. And finally, the role of the active transport versus the flow of cytosolic components in governing the stability of these nanotubes is not captured by our model and remains an active focus of our research and modeling efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Often, multiple beads are observed along a membrane nanotube, suggesting that multiple domains of heterogeneity exist along the nanotube [15,19,73,[44][45][46][47]17]. (Fig.…”
Section: Interaction Between Multiple Beads Along a Nanotubementioning
confidence: 99%